Plasma Protein and Aggregation Changes in Diabetic Patients - Abdulla, Manal; Al-Ani, Fakhir; Al-Ani, Abd Al-Satar (Iraqi Journal of Science, 2025)
Using a modified laser light scattering technique to study the red blood cells aggregation and sedimentation kinetics in normal and diabetic patients. Method: Clinical records of (40) normal volunteers and diabetic patients from Educational Kadhimya Hospital were included in this study. Results: In this method, the results of aggregation is presented in a time based graph. from which the slope (rate of aggregation can be calculated). Diabetic sample showed a shorter time of different aggregation and sedimentation stages. Samples. from diabetic patients showed a lot of variability in regard with different stages of aggregation. These changes were correlated well with the abnormality in their proteins. Conclusion: In diabetes mellitus a lot of rheological abnormalities could occur, like hyperglycemia, changes in lipid profiles and serum proteins and their sequel on the viscosity of blood on one hand and the structural and functional abnormalities of erythrocyte on the other hand. These modifications in the cellular properties and medium composition of blood in diabetic patients will affect the aggregation kinetics of erythrocytes, which may play a role in the pathogenesis of diabetic complication